Synthesis, structural characterization and luminescence properties of 1‐carboxymethyl‐3‐ethylimidazolium chloride. Issue 6 (22nd May 2018) - Prodius, Denis; Wilk-Kozubek, Magdalena; Mudring, Anja-Verena
Abstract : A carboxyl‐functionalized imidazolium chloride has been synthesized and characterized by a variety of experimental techniques. In the crystal structure, cations and anions are organized by a combination of supramolecular C—H…Cl, C—H…O, and O—H…Cl interactions to build a three‐dimensional hydrogen‐bonded network. The compound shows a short‐lived blue fluorescence and a long‐lived green phosphorescence. Abstract : A microcrystalline carboxyl‐functionalized imidazolium chloride, namely 1‐carboxymethyl‐3‐ethylimidazolium chloride, C7 H11 N2 O2 + ·Cl −, has been synthesized and characterized by elemental analysis, attenuated total reflectance Fourier transform IR spectroscopy (ATR‐FT‐IR), single‐crystal X‐ray diffraction, thermal analysis (TGA/DSC), and photoluminescence spectroscopy. In the crystal structure, cations and anions are linked by C—H…Cl and C—H…O hydrogen bonds to create a helix along the [010] direction. Adjacent helical chains are further interconnected through O—H…Cl and C—H…O hydrogen bonds to form a (10 ) layer. Finally, neighboring layers are joined together via C—H…Cl contacts to generate a three‐dimensional supramolecular architecture. Thermal analyses reveal that the compound melts at 449.7 K and is stable up to 560.0 K under a dynamic air atmosphere. Photoluminescence measurements show that the compound exhibits a blue fluorescence and a green phosphorescence associated with spin‐allowed ( 1 π← 1 π*) and spin‐forbidden ( 1 π← 3 π*) transitions, respectively. The average luminescence lifetime was determined to be 1.40 ns for the short‐lived ( 1 π← 1 π*) transition and 105 ms for the long‐lived ( 1 π← 3 π*) transition.